(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
Both nephrologists and cardiologists currently recognize that most of the known risk factors for cardiovascular diseases—such as arterial hypertension, obesity, diabetes mellitus, dyslipoproteinemia, microalbuminuria, and others—are simultaneously risk factors for the development of chronic kidney disease (CKD). The majority of prospective studies have demonstrated a positive association between serum uric acid levels and cardiovascular mortality, as well as overall mortality.